Thrombotic risk according to SERPINC1 genotype in a large cohort of subjects with antithrombin inherited deficiency - Alhenc-Gelas, Martine; Plu-Bureau, Genevieve; Hugon-Rodin, Justine; Picard, Veronique; Horellou, Marie-Helene; GFHT study group on Genetic Thrombophilia (Thrombosis and Haemostasis, 2017)
Inherited quantitative (type I) or qualitative (type II) antithrombin deficiency (ATD) due to mutations in the SERPINC1 gene is a well-known risk factor for venous thromboembolism. ATD may also increase risk for arterial thrombosis. Few studies have investigated risk for thrombosis according to mutations. We addressed this topic in a large retrospective cohort study of 540 heterozygous carriers of SERPINC1 mutations and compared risk for first venous or arterial thrombosis associated with carrying of different type II or type I mutations. No clear difference in risk for first venous thrombotic event was observed among type I (missense or null), type IIRS or type IIPE mutation carriers except for a few variants that displayed lower risk [all events, adjusted relative risk: Cambridge II: 0.42 (95%CI 0.25–0.70), Dublin: 0.35 (95%CI 0.13–0.99)]. IIHBS mutation carrying was associated with a clearly lower risk than type I mutation carrying [0.28 (95%CI 0.20–0.40)]. These differences in risk were observed for both all venous thrombotic events and pulmonary embolism associated with deep venous thrombosis. The HBS group was also heterogeneous, with AT Budapest 3 carriers displaying a non-significantly different risk [0.61 (95%CI 0.31–1.20)] compared to type I mutation carriers. We also studied risk for arterial thrombosis and found no significant influence of mutation type. Altogether, our findings suggest a place for SERPINC1 genotyping in the diagnosis of ATD.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Coagulation inhibitor; antithrombin; SERPINC1; thrombophilia; thrombosis